2011
DOI: 10.1371/journal.pone.0019900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Topology and Delayed Interactions in Neuronal Networks Synchronization

Abstract: As important as the intrinsic properties of an individual nervous cell stands the network of neurons in which it is embedded and by virtue of which it acquires great part of its responsiveness and functionality. In this study we have explored how the topological properties and conduction delays of several classes of neural networks affect the capacity of their constituent cells to establish well-defined temporal relations among firing of their action potentials. This ability of a population of neurons to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 40 publications
0
42
1
Order By: Relevance
“…This difference is mainly result from phase slips induced by the time delay. Indeed, the delay-induced multiple synchronization states of neuronal activity are due to an intricate interplay between the inherent dynamics of constituting neurons and the locking between the delay time and the oscillatory period of neuronal spiking (Pérez et al 2011;Wang et al 2008Wang et al , 2009Wang et al , 2010. On the other hand, for both coupling types the local synchronization transition is more profound than the global synchronization transition, as the value of S glob is no larger than 0.5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference is mainly result from phase slips induced by the time delay. Indeed, the delay-induced multiple synchronization states of neuronal activity are due to an intricate interplay between the inherent dynamics of constituting neurons and the locking between the delay time and the oscillatory period of neuronal spiking (Pérez et al 2011;Wang et al 2008Wang et al , 2009Wang et al , 2010. On the other hand, for both coupling types the local synchronization transition is more profound than the global synchronization transition, as the value of S glob is no larger than 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the phase synchronization between neuron i and the set of its neighbors v(i), we calculate the quantity (Pérez et al 2011):…”
Section: Mathematical Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, phase relationships contain a great deal of information on the temporal structure of neural signals, modulate neuron interactions, are associated with cognition and relate to memory formation and retrieval (Izhikevich, 1999;Womelsdorf et al, 2007;Masquelier et al, 2009;Kayser et al, 2009). Moreover, recent works have shown that specific topological properties of local and distant cortical areas support synchronisation despite the inherent axonal conduction delays, thereby providing a substrate upon which neuronal codes relying on precise interspike time can unfold (Vicente et al, 2008;Pérez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%